Introducing Green Practices for Construction Project Implementation Through Collaborative Approach - Zafikha Aida, Bidin; Khalid, Zanudin; Asmah Alia, Mohamad Bohari; Hong-Trang, Nguyen (2022)
Successful construction project implementation depends on support from the stakeholders to meet the project objectives. Among the challenges identified related to stakeholders is the level of knowledge and awareness on working together to meet the project objective. The green initiative has been considered one of the project’s missions to tackle the environmental degradation issue due to the construction process. One of the green initiatives is the introduction of green practices. Thus, this conceptual paper highlights the importance of a collaborative approach for empowering the understanding, awareness, and willingness of construction stakeholders and the government to implement green practices in the construction process. The framework is developed through a literature review as the method to collect and analyse the literature data. The paper concluded that a collaborative approach enables all actors, particularly the construction stakeholders, to be educated, aware, and willing to implement green practices in the construction process.